Methicillin-Resistant Staphylococcus aureus in Obstetrics - Sheffield, Jeanne S. (American Journal of Perinatology, 2013)
Methicillin-resistant Staphylococcus aureus (MRSA) remains one of the major multiple antibiotic-resistant bacterial pathogens causing serious community-associated and health care-associated infections. It is now pervasive in the obstetric population associated with skin and soft tissue infections, mastitis, episiotomy, and cesarean wound infections and urinary tract infections. This review addresses the epidemiology, definitions, microbiology, and pathogenesis as well as common clinical presentations. A discussion of the 2011 Infectious Diseases Society of America MRSA treatment guidelines details available antibiotics, invasive and noninvasive MRSA management, and specific factors related to obstetrics. Finally, prevention strategies including decolonization are discussed.
Keywords: MRSA; methicillin resistance; antibiotic resistance; CA-MRSA